Phenotype Gene Expression Differences Between Resistant and Susceptible Salmon Families to Ipnv - Cofre-Montenegro, C; Vidal-Soto, R (Kluwer Academic Publishers, 2014)
Infectious pancreatic necrosis virus (IPNV) is an economically important pathogen of the salmonid aquaculture industry. Selective breeding has been employed to improve resistance to this infectious disease, and it is of importance to investigate the expression profile of immune genes of Atlantic salmon with different genetic background in response to this virus. This study examined the immune modulation response of eight candidate genes in head kidney tissue in two families of Atlantic salmon with high and low mortalities, after challenge with IPNV. The results showed that the expression pattern of target genes differed in the two families. Generally, higher expression of antiviral, pro-inflammatory genes and transcription factors such as tripartite motif, NF-?B, IFNI, STAT1, protein kinase R, and Vig-2 in the resistant family were observed at the same time point. One may speculate the functional importance of these putative candidate genes in the characterization of the IPNV-resistant (low mortalities) immune phenotype. Therefore, on our findings, we suggest that future salmonids studies aiming to identify candidate genes/pathway or vaccines evaluation should consider validating detected genes/pathway across different genetic backgrounds or immune phenotype. © 2013 Springer Science+Business Media Dordrecht.